Correlation between DWI‐MRI and Findings at Cholesteatoma Surgery: Should DWI‐MRI Be Standardized Prior to Surgery?. (2nd September 2014) - Deleito, Javier M.; Ray, Jaydip; Twigg, Victoria; Wu, Kenneth
Abstract : Objectives: Evaluate the accuracy of diffusion‐weighted imaging magnetic resonance imaging (DWI‐MRI) in diagnosis of cholesteatoma and the planning of surgery in our hospital. Methods: We conducted a retrospective study of all patients who had cholesteatoma surgery in our hospital from November 2007 until September 2013 that had undergone a DWI‐MRI previous to the surgery. Results: A total of 24 patients were found. A total of 22 DWI‐MRI findings were correctly correlated to findings in operation. There was 1 false positive where cholesteatoma was identified on imaging and mucosal disease was found in surgery; and 1 false negative that failed to identify a small cholesteatoma found during surgery. Of the 22 accurate correlations, 4 were of mucosal disease and the rest were correctly diagnosed as cholesteatomas. The DWI‐MRI was able to localize the location of the cholesteatoma (from middle ear, attic, mastoid, aditus, hypotympanium and Eustachian tube) in 78% of the cases (14/18). Conclusions: DWI MRI is highly sensitive in the identification of the presence of cholesteatoma. Negative findings should be followed up because imaging sequences can miss cholesteatomas smaller than 3 mm. There is still a learning curve in the diagnosis and use of DWI MRI.